PENGETAHUAN REMAJA TENTANG PERSONAL HYGIENE SAAT MENSTRUASI PADA SISWI MTs MUHAMMADIYAH 2 KALIJAME SRAGEN - Mursudarinah Mursudarinah; Dini Aidila Fitria Hastuti (Universitas Duta Bangsa Surakarta, 2021)
Personal hygiene during menstruation plays an important role in the status of aperson's health behavior, including avoiding disturbances in the function of thereproductive organs. Hygiene of the genitals must be more maintained becausegerms can easily enter and can cause reproductive tract infections. The results ofa preliminary study conducted by interviewing 20 students of MTsMuhammadiyah 2 Kalijambe Sragen. 5 students (25%) of whom change sanitarynapkins 2x1 day or if uncomfortable, clean the vagina from front to back and 15students (75%) do not know personal hygiene during menstruation. This studyaims to determine the level of adolescent knowledge about personal hygieneduring menstruation at MTs Muhammadiyah 2 Kalijambe Sragen students. The research design is descriptive quantitative. The sample is all students at MTsMuhammadiyah 2 Kalijambe Sragen as many as 115 respondents. The samplingtechnique is a non-probability technique by means of saturated sampling (totalsampling). The research instrument was a closed questionnaire using univariateanalysis.The results showed that adolescents' knowledge of personal hygiene duringmenstruation was in the good category, namely 17 students (15%), enough for 61students (53%), less, namely 37 students (32%).Description of Adolescent Knowledge about Personal Hygiene duringMenstruation at MTs Muhammadiyah 2 Kalijambe Sragen Students, namely in thesufficient category. Adolescents are expected to be able to understand personalhygiene during menstruation so that adolescents can carry out hygiene andmaintain health.